Peningkatan Keterampilan Berpikir Kritis dalam Matematika Sekolah Menengah melalui Discovery Learning Berbantuan LKPD - Ismawati, Arfina Maya; Suyitno, Hardi; Hastuti, Wijaning (Jurnal Tadris Matematika, 2024)
This research is motivated by the results of observations that indicate that the critical thinking skills of students at SMAN 2 Yogyakarta still need to be improved. This is seen during learning practices, where they are still fixated on the formulas they have memorized to solve problems, so that not many students can provide further explanations about solving the problem. On the other hand, the pretest results also show that the average value of students' critical thinking skills is still very low, namely 30.76% with 1 student having high critical thinking skills and 33 others still classified as low and very low. Therefore, this Classroom Action Research (CAR) is a study that aims to improve critical skills in high school mathematics through discovery learning assisted by LKPD. This research was conducted in two cycles, each cycle consisting of four stages: planning, implementation, observation, and reflection. The results of the study show an increase in critical thinking skills from cycle I to cycle II. In cycle I, the average percentage of students' critical thinking skills reached 73.64% (medium category), while in cycle II, it increased to 80.72% (high category). Thus, this classroom action research succeeded in achieving the expected goal, namely, improving critical thinking skills in secondary school mathematics through the application of the Discovery Learning model assisted by LKPD